Generalized Anxiety Disorder Among University Students Due To COVID-19 (Pragya Darshan प्रज्ञा दर्शन, 2023)
Generalized Anxiety Disorder (GAD) is a common but urgent mental health problem during disease outbreaks. With the outbreak of COVID-19’s second wave, educational institutions were closed, and the students had to remain confined to online teaching[1]learning, which might create many psychological problems. This study assesses the prevalence of generalized anxiety disorder among university youth students due to COVID-19. A cross-sectional online survey was conducted among 176 (response rate: 76.5%) university students studying at the Central Department of Education. The Generalized Anxiety Disorder scale (GAD-7) questionnaire was used to assess anxiety disorder. Students were selected using a simple random sampling technique and sent the questionnaire link created in the Kobo toolbox to them requesting voluntary participation. The collected responses were analyzed using descriptive statistics and multivariate logistic regression to find the GAD prevalence and associated factors. A study found that 47.7% of university students had generalized anxiety disorder due to COVID-19. Older participants had a lower likelihood of anxiety disorder compared to those under 30 (OR 0.267). Buddhists had higher odds than Hindus (OR 5.237), and students in Bagmati and Lumbini Provinces had higher odds than those in Koshi Province (OR 8.116 and OR 6.086, respectively). Students not infected with COVID-19 had higher odds of anxiety disorder than infected students (OR 7.564), and those not vaccinated had higher odds than those vaccinated (OR 2.883). Taken together, age, religion, province of residence, COVID-19 vaccination status, and perceived risk due to COVID-19 played a role in determining the prevalence of generalized anxiety disorder among students.